Comprehensive analysis of Mendelian randomization and scRNA-seq identify key prognostic genes and relevant functional roles in colorectal cancer - Meng Hu; Haotian Dong; Chujia Chen; Chengyuan Ye; Jianing Yan; Xuan Yu; Guoliang Ye; Yongfu Shao (Scientific Reports)
Abstract The prognosis of advanced CRC is poor, and identifying key genes related to CRC is vital for improving CRC prognosis. Our research used univariate Cox analysis and Mendelian randomization (MR) analysis to identify key prognostic genes in CRC. Multiple datasets such as the nomogram model and single-cell sequencing (scRNA-seq) were used to investigate the potential molecular mechanisms of the key genes. The expression levels were confirmed by using quantitative real-time polymerase chain reaction (qRT-PCR). The biological functions and effect on prognosis of the identified prognostic genes were also explored. MMRN1 and SLC6A19 were identified as key prognostic genes for CRC. Subsequently, the nomogram model demonstrated that MMRN1 and SLC6A19 can strongly predict survival. Further examination with multiple datasets elucidated the potential molecular mechanisms of the key prognostic genes, revealing a close association with immune cell infiltration. MMRN1 is enriched in classic CRC signaling pathways, whereas SLC6A19 is enriched in metabolism-related pathways. They are closely linked to immune cell infiltration levels and significantly influence the immune microenvironment in CRC. These key prognostic genes are significantly correlated with chemotherapeutic drug sensitivity and present promising opportunities for CRC therapy. The expression of both key genes was also observed in the scRNA-seq data of CRC. Finally, qRT-PCR validation revealed that MMRN1 is markedly downregulated and SLC6A19 is significantly upregulated in CRC. Lower expression of MMRN1 and higher expression of SLC6A19 significantly promoted the proliferation and metastasis of colorectal cancer cells. Our study identified MMRN1 and SLC6A19 as potential key prognostic genes for CRC, as they can reliably predict the prognosis of CRC. Furthermore, the potential molecular mechanisms of MMRN1 and SLC6A19 were revealed, suggesting new drug targets and therapeutic directions for managing prognosis.